Prolonged Antiretroviral Therapy Preserves HIV-1-Specific CD8 T Cells with Stem Cell-Like Properties - Vigano, Selena (J Virol, 2015)
HIV-1-specific CD8 T cells can influence HIV-1 disease progression during untreated HIV-1 infection, but the functional and phenotypic properties of HIV-1-specific CD8 T cells in individuals treated with suppressive antiretroviral therapy remain less well understood. Here we show that a subgroup of HIV-1-specific CD8 T cells with stem cell-like properties, termed T memory stem cells (T(SCM) cells), is enriched in patients receiving suppressive antiretroviral therapy compared with their levels in untreated progressors or controllers. In addition, a prolonged duration of antiretroviral therapy was associated with a progressive increase in the relative proportions of these stem cell-like HIV-1-specific CD8 T cells. Interestingly, the proportions of HIV-1-specific CD8 T(SCM) cells and total HIV-1-specific CD8 T(SCM) cells were associated with the CD4 T cell counts during treatment with antiretroviral therapy but not with CD4 T cell counts, viral loads, or immune activation parameters in untreated patients, including controllers. HIV-1-specific CD8 T(SCM) cells had increased abilities to secrete interleukin-2 in response to viral antigen, while secretion of gamma interferon (IFN-γ) was more limited in comparison to alternative HIV-1-specific CD8 T cell subsets; however, only proportions of IFN-γ-secreting HIV-1-specific CD8 T(SCM) cells were associated with CD4 T cell counts during antiretroviral therapy. Together, these data suggest that HIV-1-specific CD8 T(SCM) cells represent a long-lasting component of the cellular immune response to HIV-1 that persists in an antigen-independent fashion during antiretroviral therapy but seems unable to survive and expand under conditions of ongoing viral replication during untreated infection. IMPORTANCE Memory CD8 T cells that imitate the functional properties of stem cells to maintain lifelong cellular immunity have been hypothesized for many years, but only recently have such cells, termed T memory stem cells (T(SCM) cells), been physically identified and isolated in humans, mice, and nonhuman primates. Here, we investigated whether cellular immune responses against HIV-1 include such T memory stem cells. Our data show that HIV-1-specific CD8 T memory stem cells are detectable during all stages of HIV-1 infection but occur most visibly at times of prolonged viral antigen suppression by antiretroviral combination therapy. These cells may therefore be particularly relevant for designing antiviral immune defense strategies against the residual reservoir of HIV-1-infected cells that persists despite treatment and leads to viral rebound upon treatment discontinuation.